2017
DOI: 10.1016/j.actbio.2016.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Model polymer system for investigating the generation of hydrogen peroxide and its biological responses during the crosslinking of mussel adhesive moiety

Abstract: Mussel adhesive moiety, catechol, has been utilized to design a wide variety of biomaterials. However, the biocompatibility and biological responses associated with the byproducts generated during the curing process of catechol has never been characterized. An in situ curable polymer model system, 4-armed polyethylene glycol polymer end-capped with dopamine (PEG-D4), was used to characterize the production of hydrogen peroxide (H2O2) during the oxidative crosslinking of catechol. Although PEG-D4 cured rapidly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
50
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 65 publications
3
50
0
Order By: Relevance
“…Additionally, the cytotoxicity effect of H 2 O 2 released from the PDA-coated mesh was highly localized, potentially due to the instability of H 2 O 2 (Reznikov et al, 2000) and its short diffusion radii in the culture medium (Takano et al, 2002). The same localized cytotoxicity response has been observed for catechol-containing hydrogels (Meng et al, 2017).…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…Additionally, the cytotoxicity effect of H 2 O 2 released from the PDA-coated mesh was highly localized, potentially due to the instability of H 2 O 2 (Reznikov et al, 2000) and its short diffusion radii in the culture medium (Takano et al, 2002). The same localized cytotoxicity response has been observed for catechol-containing hydrogels (Meng et al, 2017).…”
Section: Resultssupporting
confidence: 76%
“…The meshes were placed vertically along the wall of the well so that the cells can be in direct contact with the H 2 O 2 released from the PDA coatings. Biocompatibility of the PDA-coated meshes was investigated using live/dead cell viability assay according to previously published protocol (Meng et al, 2017). L929 rat dermal fibroblasts were seeded into a 12-well plate with a density of 1 × 10 4 cell/well and incubated at 37°C in a 5% CO 2 humidified incubator for 24 h to obtain a monolayer of cells.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, covalent crosslinking via dimer formation and polymerization of catechol moieties occurs more rapidly at an elevated pH [42], which decreased the number of catechol that could be further oxidized to generate H 2 O 2 . We previously reported that chemical oxidant-induced oxidation and crosslinking of catechol exhibited a similar initial burst release of H 2 O 2 followed by a drastic reduction in measured H 2 O 2 over time [50]. Microgels did not release H 2 O 2 at pH 3.5 as catechol remained in its reduced form as demonstrated from the UV-vis spectra (Figure S5a).…”
Section: Resultsmentioning
confidence: 73%
“…Our UV-vis data (Figure S5b) indicated the formation of α,β-dehydrodopamine (yellow) during autoxidation, potentially due to its increased stability at a basic pH when compared to dopamine quinone [54]. α,β-dehydrodopamine regained a catechol moiety that could be further oxidized to α,β-dehydrodopamine quinone, generating H 2 O 2 during the process [50, 54]. The subsequent cycles of pH changes likely involved the oxidation and reduction of α,β-dehydrodopamine.…”
Section: Resultsmentioning
confidence: 99%
“…[21] However, the application of cytotoxic chemical oxidant such as the oft-used NaIO 4 may not be desirable for many biomedical applications. [22] Additionally, in situ activation using an oxidizing reagent requires mixing of two precursor solutions during application. Ion-induced slow, oxidative crosslinking of catechol have been recently reported to form hydrogels that transitioned from a physically crosslinked network into a predominantly covalently crosslinked network.…”
mentioning
confidence: 99%